Re-synthesis of Cathode Precursors from End-of-life Lithium-ion Battery Electrode Powders: Effect of Leaching Conditions on the Co-precipitation of Nickel-manganese-cobalt Mixed Oxalate - Marco Colasanti; Ludovica D'Annibale; Alyssa Mancini; Federica M. Canale; Raimondo Milone; Pier Giorgio Schiavi; Pietro Altimari; Francesca Pagnanelli (Chemical Engineering Transactions)
The lithium-ion battery (LIB) market is experiencing rapid growth due to the increasing interest in electric and hybrid vehicles. LIBs are categorized by their cathodic materials into four main types: LCO (cobalt-based), NMC (nickel, manganese, cobalt), NCA (nickel, cobalt, aluminum), and LFP (iron phosphate). The widespread production and use of LIBs will inevitably result in a significant increase in end-of-life LIBs, which have to be recycled. Hydrometallurgical recycling processes offer an innovative solution for metal recovery from end-of-life LIBs. In particular, processes that include the resynthesis of cathodic materials can enhance sustainability by directly recovering mixed precursors of cathodes from leach liquors. The chemical composition of leach liquors, specifically the concentrations of Ni, Mn, and Co, as well as the levels of impurities such as Fe, Cu, and Al, can influence the final properties of the mixed precursors. In this study, two different leach liquors and one synthetic solution were used for precursor production via oxalate precipitation. The results indicate that according to the leaching composition the stoichiometry and conversion efficiency of the precipitation reaction can very, while no significant difference is observed in morphology and size of particles.